Specificità dell’arte sacra cristiana - Gagliardi, Mauro (Alpha Omega, 2017)
Summary: The article is an expanded version of a speech given at an International Sym-posium of University Professors, in 2011. It presents the essential elements of the Chris-tian concept of sacred art, which, in a nutshell, correspond to the derivation of Christian sacred art from the faith in the incarnated Logos (Who is also the Creator of everything), with all its theoretical and practical implications. The presentation of this central aspect is preceded by a synthetic overview of the philosophical concept of beauty and art, and followed by a short consideration of the present state of sacred art in the Catholic Church and of the means to heal the present state of infirmity of Catholic sacred art. Key words: Sacred Art, Beauty, Aesthetics, Plato, Aristotle, Plotinus, Thomas Aquinas, Ratzinger, Magisterium, Patronage of the arts. Parole chiave: Arte sacra, Bellezza, Estetica, Platone, Aristotele, Plotino, Tommaso d’Aquino, Ratzinger, Magistero, Mecenatismo.